Strategic Positioning and Operational Challenges of Water Utility Companies: A Case of West Java, Indonesia - Didin Kristinawati (Journal of Enterprise and Development (JED), 2024)
Purpose: This study aims to analyze the strategic positioning and operational challenges faced by Water Utility Company X (WUCX) in West Java, Indonesia. It identifies key strengths, weaknesses, opportunities, and threats (SWOT) that affect the company's ability to meet the increasing demand for reliable water services in a rapidly urbanizing region.Method: The study employs a mixed-methods approach, combining qualitative and quantitative data. Qualitative data were gathered through semi-structured interviews with WUCX senior management, focusing on internal and external factors impacting the company. Quantitative data were drawn from company documents, such as financial reports and surveys. The analysis, based on a SWOT framework, offers a comprehensive assessment of WUCX’s strategic position.Result: The SWOT analysis revealed that WUCX has notable strengths, including an efficient billing system, strong financial stability, and extensive technical service coverage. These strengths position the company to seize opportunities for service expansion through strategic partnerships. However, the analysis also identified key weaknesses, such as aging infrastructure and significant water loss, which could threaten long-term sustainability. Externally, the company faces opportunities like supportive legal frameworks and rising demand, but also threats such as environmental degradation and challenges in coordinating water sourcing.Practical Implications for Economic Growth and Development: This study offers actionable insights to enhance the strategic positioning and operational efficiency of public utilities like WUCX. These insights can drive improvements in infrastructure management, service delivery, and financial sustainability, ultimately contributing to broader economic growth and development in rapidly urbanizing regions.